2009
DOI: 10.1155/2009/107286
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hypertension in Aggravating Aβ Neuropathology of AD Type and Tau-Mediated Motor Impairment

Abstract: Epidemiological evidence suggests that hypertension may accelerate the onset and progression of Alzheimer's disease (AD). In this study, we explored the role of hypertension in the neurodegenerative changes associated with Aβ and tau aggregation. We induced hypertension in APPswe Tg2576 and P301L-tauTg mouse models. In Tg2576 mice, experimental hypertension was associated with a significant increase of the accumulation of Amyloid-β (Aβ) peptides in brain tissue and a significant reduction of Aβ peptides in ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 19 publications
1
36
0
Order By: Relevance
“…Neuropathological studies have shown that up to 30% of AD patients exhibit evidence of cerebral infarction, especially striatal lacunar infarction, at autopsy, and that patients with both AD and cerebral infarction show more severe cognitive impairment than those with AD alone (Heyman et al, 1998;Snowdon et al, 1997). It was suggested that hypoxia and vascular risk factors, such as hypertension and diabetes, can accelerate AD development in vivo (Cao et al, 2007;Diaz-Ruiz et al, 2009;Li et al, 2009). Our clinical studies also found that vascular risk factors aggravated the progression of AD (Li et al, 2010(Li et al, , 2011.…”
Section: Introductionsupporting
confidence: 53%
“…Neuropathological studies have shown that up to 30% of AD patients exhibit evidence of cerebral infarction, especially striatal lacunar infarction, at autopsy, and that patients with both AD and cerebral infarction show more severe cognitive impairment than those with AD alone (Heyman et al, 1998;Snowdon et al, 1997). It was suggested that hypoxia and vascular risk factors, such as hypertension and diabetes, can accelerate AD development in vivo (Cao et al, 2007;Diaz-Ruiz et al, 2009;Li et al, 2009). Our clinical studies also found that vascular risk factors aggravated the progression of AD (Li et al, 2010(Li et al, , 2011.…”
Section: Introductionsupporting
confidence: 53%
“…A number of autopsy studies [20,21] have shown that the probability of manifesting clinical dementia for a given level of AD pathology increases with the presence of cerebrovascular pathology, both of which are strongly linked to hypertension [2230] and arterial stiffness (discussed in detail in the ‘Arterial stiffness & the brain’ section). While there is little mechanistic evidence supporting the observed relationships between blood pressure with the formation of Tau proteins or neurofibrillary tangles in the brain [31,32] , blood pressure may be related to AD pathogenesis or progression through mechanisms involving Aβ synthesis, clearance or its deposition as plaques [33] . Uncontrolled hypertension appears to predict the level of neurofibrillary tangles and neuritic Aβ plaques [3436] in the brain, which implies hypertension could have direct effects on AD pathology.…”
Section: Understanding the Links Between Hypertension And Admentioning
confidence: 99%
“…High pulsations in the microvessels of brain and kidneys cause damage to the endothelium with shedding of endothelial cells (the ultimate endothelial dysfunction), causing subsequent thrombosis and microinfarction [47] . High pulsatile pressure stretches and damages all classes of arteries, similar to the effects seen in malignant hypertension and intracerebral hemorrhage [31] resulting in lacunar stroke [24] , microhemorrhage [23] and white matter hyperintensities (WMH) on MRI [22,25] , which are commonly found at autopsy in persons with AD.…”
Section: Factors Underlying Hypertensionmentioning
confidence: 99%
“…Similarly, stroke risk factors have shown strong associations with brain volume (Seshadri et al, 2004), neuropsychological impairment (Brady et al, 2001; Jefferson et al, In Press ; Kivipelto et al, 2002), and cerebrovascular pathology (Wang et al, 2009; Wolf et al, 1991). In mouse models, there has been some evidence that certain stroke risk factors, such as smoking (Moreno-Gonzalez et al, 2013) and hypertension (Diaz-Ruiz et al, 2009; Gentile et al, 2009), actually exacerbate AD pathology. Thus, there may be differing effects of stroke risk factors on neurodegeneration depending on the presence or absence of AD biomarkers.…”
Section: Introductionmentioning
confidence: 99%